(untitled) (Revista Lusófona de Educação, 2025)
Without intending to be an academic article in the strict sense, this text is essentially essayistic in nature and has some biographical and autobiographical marks that are based on brief and specific childhood memories, with the main purpose of paying a simple tribute to a primary school teacher, on the centenary of her birth (1925-2025). In the process of writing (and naturally as a layman in the historian’s profession), I felt the risk of summoning memories and discontinuous moments that, when revisited with the intention of achieving the necessary narrative congruence, are not, many decades later, immune to possible drifts of a diachronic reinterpretation, where the factual, intuition and imagination inevitably mix. For this reason, I sought the contribution, albeit punctual, but indispensable, of the History of Education, because only research can lend rigor to an exercise of this kind.